A cable-pulley transmission mechanism for surgical robot with backdrivable capability. (February 2018) - Li, Hongbing; Liu, Weiwen; Wang, Kundong; Kawashima, Kenji; Magid, Evgeni
Highlights: A differential mechanism having a cable comprises a sheave wheel supported by a yolk is implemented. A miniaturized, low friction, back-drivable reducing mechanism for haptic or surgical robot applications has been designed. The driving cables are wound on two synchronized drums which impose different windings and unwinding lengths to vary the total cable length. Abstract: Compact actuators, low friction and back-drivable transmissions are essential components in haptic and impedance type surgical robotic systems, since their performances affect overall volume, force feedback capability and power consumption. An innovative miniaturized, low friction, back-drivable reducing mechanism for haptic or surgical robot applications has been designed, developed and evaluated. A new differential mechanism having a cable comprises a sheave wheel supported by a yolk is also implemented. Low friction and back-drivable, compared to conventional non-back-drivable mechanisms based on gear coupling, is achieved by means of differential cable driven method. The system has been integrated with a permanent-magnet DC motor and a drum on which a tendon is wound, and then finally connected to the remote end joint. Several experiments to validate the feasibility of the reducing device were carried out.